PENGARUH PERUBAHAN TATA GUNA LAHAN TERHADAP DISPARITAS REGIONAL ANTARKECAMATAN DI KOTA TANGERANG SELATAN - Muhammad Bintang Wibowo Nugraha; Zulqadri Ansar; Nela Agustin Kurnianingsih (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
Regional disparity is a phenomenon of economic differences between regions (Bakri, et.al 2016). The Bappeda of Banten Province stated that South Tangerang City experienced a relatively high regional disparity level (Noviar, 2021). Triyanto, et.al (2019) stated that land use changes influenced regional disparity. However, this influence has not been identified in South Tangerang City. This study aims to identify the influence of land use change on regional disparity between sub-districts in South Tangerang City in 2015 and 2019. The data collection technique uses secondary data from related agencies with regional disparity, spatial and multiple linear regression statistical analysis techniques. The results of the analysis show that regional disparity consist of low, medium and high levels. Then, land use changes in 2019 are built-up land use change with an area of ​​493.29 ha (84.75%) and non-built-up land use change with an area of ​​88.73 ha (15.25%) out of a total of 582, 02 ha (100%). Furthermore, the influence of built-up land use change (X1) and non-built-up land use change (X2) simultaneously or partially has a significant influence on regional disparity (Y) which is 86%, while the remaining 14% is influenced by other independent not examined variables.